Factors Causing Damage To Medical Record Documents In The Filling Room At Dr.R.M. Djoelham Binjai Hospital - Simanjuntak, Marta; Dawolo, Fitra Christin (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Medical record documents must be managed properly so that they are not damaged or lost so that they can be reused for treatment or providing other services. From the interview results, damage to medical record documents included the folder or cover of the medical record document being damaged or torn, there were piles of files on the floor so that the medical record folder was dirty and crumpled. This study aims to determine the factors that cause damage to medical record documents at Dr.R.M. Hospital. Djoelham Binjai uses 5 management elements Man, Method, Machine, Material, and Money. This type of research uses qualitative research with a descriptive approach. The subjects in this research were officers in the filling room at RSUD Dr. R.M. Djoelham Binjai, totaling 5 people and the object of this research is medical record documents in the filling room at Dr. RSUD. R.M. Djoelham Binjai. The data collection methods used in this research are observation and interviews. The results of the research show that the factors causing damage to medical records are based on the 5M factor, namely the human factor, there are still many officers who are not D3 medical record graduates, officers do not immediately replace damaged folders. Factors include limited shelf storage and a lot of documents piling up. The storage room method factor already has an SOP but its implementation is not carried out, and retention is not carried out. The material factor of the map material used is in accordance with standard hospital procedures. The money factor does not yet have a special budget for replacing damaged maps. To the officers in the filling room, it is best to retain or shrink medical record documents so that the storage shelves are a little loose and there are no medical record documents piled up on the floor, so that medical record documents are maintained.